2022
DOI: 10.1177/19386400211068256
|View full text |Cite
|
Sign up to set email alerts
|

May the Symptomatic Subtalar Joint Be Conservatively Treated With Intra-Articular Hyaluronic Acid Injections After a Calcaneus Fracture?

Abstract: Background Subtalar pain following intra-articular calcaneus fractures may be associated with disability, pain, and a negative impact on the quality of life. Salvage procedures as subtalar fusion are associated with further consequences as stiffness, altered ankle biomechanics, and adjacent articular overloading with degenerative changes. The objective of the present study is to evaluate the short-term effects of viscosupplementation with intra-articular hyaluronic acid (HA) on function and pain, in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Mei-Dan and colleagues demonstrated that patients submitted to viscosupplementation with 10mg sodium hyaluronate (Euflexxa) administered weekly to the subtalar joint for 3 weeks improved the American Orthopaedic Foot and Ankle Society Ankle Hindfoot score (AOFAS) and on Visual Analogue Scale (VAS) till 28 weeks after injection [5]. Other studies regarding the same protocol scheme showed that similar results were achieved by the use of 20mg sodium hyaluronate (Polireumin) [2] or by the combination of 20mg sodium hyaluronate (Polireumin) with 10mg of betamethasone sodium phosphate ]3]. However, isolated corticoid injection effect was limited to 4 weeks, having returned to the original parameters after 12 weeks of the first injection [3].…”
mentioning
confidence: 94%
“…Mei-Dan and colleagues demonstrated that patients submitted to viscosupplementation with 10mg sodium hyaluronate (Euflexxa) administered weekly to the subtalar joint for 3 weeks improved the American Orthopaedic Foot and Ankle Society Ankle Hindfoot score (AOFAS) and on Visual Analogue Scale (VAS) till 28 weeks after injection [5]. Other studies regarding the same protocol scheme showed that similar results were achieved by the use of 20mg sodium hyaluronate (Polireumin) [2] or by the combination of 20mg sodium hyaluronate (Polireumin) with 10mg of betamethasone sodium phosphate ]3]. However, isolated corticoid injection effect was limited to 4 weeks, having returned to the original parameters after 12 weeks of the first injection [3].…”
mentioning
confidence: 94%
“…As a biomaterial, HA gel has the advantages of good biocompatibility, strong water absorption, and high viscosity, which can provide an ideal biological scaffold to provide the necessary support and growth environment for fracture healing (14,15). In addition, HA gel can also promote the proliferation, differentiation and mineralization of bone cells in a variety of ways, thereby accelerating fracture healing (16).…”
Section: Introductionmentioning
confidence: 99%